Analisa Rugi-Rugi Daya Dan Jatuh Tegangan Pada Saluran Transmisi 150 kV GI Pati Bay GI Jekulo Menggunakan ETAP 12.6.0 - Anggoro, Bayu Andik; Utomo, Sukarno Budi; Widihastuti, Ida (Universitas Semarang, 2020)
In the electric power system, the transmission system is a pathway to transmit electrical energy from the generator to the substation or from the substation to another substation which allows power losses and large voltage drops if the transmission length is relatively far and the overload is very high. affect the reliability of the transmission system. Analysis of power losses and voltage drop on the 150 KV high voltage transmission system at the Pati substation to the Jekulo substation. The analysis was carried out by conducting a survey at the research location then doing manual calculations and calculations using ETAP 12.6.0 software. The research method used was that the researcher collected voltage and current data at 10.00 and 19.00 WIB in one month and the transmission system supporting equipment specifications to be simulated in ETAP 12.6.0 from Pati and Jekulo substations in order to make comparisons between manual calculations and ETAP. 12.6.0.The conclusion of this study is the calculation of power losses manual calculation and simulation of ETAP 12.6.0 has a difference of 2.5% with the value of manual calculation power losses of 685.5 KW and the power losses from The simulation results reached 266.6 KW and the calculation of the presentation of power losses in the transmission line of GI Pati - GI Jekulo reached 6.8% exceeding the service percentage variation limit due to losses according to SPLN No. 72 of 1987 a maximum of 5% at least -10%.